Effects of soil bulk density and water content on penetration resistance. Issue 2 (24th November 2022) - Lardy, Jarrett M.; DeSutter, Thomas M.; Daigh, Aaron L. M.; Meehan, Miranda A.; Staricka, James A.
Abstract: Infrastructure installation (e.g., pipelines) disturbs soils, often resulting in increased soil compaction (bulk density [Bd] and penetration resistance [PR]). The relationship of PR to Bd, gravimetric water content (Θg), and a suite of other properties were determined on seven topsoils to provide a model and database for reclamation specialists to use when assessing disturbed soils. Penetration resistance had a strong linear association with Bd, but higher Θg reduced the range of PR as Bd increased. Step‐wise regression identified Bd, Θg, texture, clay speciation, and organic matter as significant factors to predict PR. The model predicts PR from <1 to 8 MPa and closely match measured values. Soil Bd and Θg contributed to 84% of the model's explained variation in predicting PR. This study provides a tool for reclamation specialists that aids in understanding the risks associated with disturbances and highlights the importance of keeping Θg low during installation of pipelines. Core Ideas: Penetration resistance decreased as water content approached saturation. Penetration resistance can be predicted from bulk density and water content using inexpensive equipment. Assessing penetration resistance before planting can aid in management decisions.